Upaya Penanganan dan Perilaku Pasien Penderita Diabetes Mellitus Tipe 2 di Puskesmas Maccini Sawah Kota Makassar - Fachruddin, Ismi Irfiyanti; Sari, A. Desi Purnama (Universitas Aisyah Pringsewu (UAP) Lampung, 2021)
Prevalence of DM is getting higher even in advanced country and developed country, especially in Indonesia. DM occupies the fifth rank from ten main causes of death in Makassar . This research has purpose to indentify the effort of caring and behaviour of patients of DM type 2 at Maccini Sawah Health Center Makassar. The research method is descriptive observasional survey, with a sample of 29 respondents. There are 2 kinds of samples in this research, health officers and patients of DM type 2. The technique of choosing the samples by using purposive sampling technique. Research process of effort caring of DM type 2 to health officers which is done through direct observation and research to patients behaviour through direct interview to the patients and examining of GDS. The result of the research proved that caring effort of DM at Maccini Sawah Health Center is still less satisfying. The patients of DM type 2 are still less knowledge and most of them are still disobidient to the instruction given. The prevalence of the patients who have uncontrolled GDS are higher than controlled patients. This research recommended to maximize the role of health of TPG in service in nutritional corner. In addition it’s better that the service in nutritional corner in not only for the babies or pregnant women, but also functional to serve other patients, especially for DM patients, and is expected to further research on interventions in patients with DM. Abstrak: Prevalensi diabetes mellitus sudah semakin tinggi, baik di negara-negara maju, maupun di negara-negara berkembang khususnya Indonesia. Diabetes mellitus menempati peringkat lima dari sepuluh penyebab utama kematian di Makassar. Penelitian ini bertujuan untuk mengetahui upaya penanganan dan perilaku pasien penderita DM tipe 2 di Puskesmas Maccini Sawah Kota Makassar. Jenis penelitian adalah observasional deskriptif dilakukan dengan sampel sebanyak 29 responden. Teknik pengambilan sampel dengan menggunakan teknik purposive sampling. Hasil penelitian didapatkan upaya penangan DM di Puskesmas Maccini Sawah masih kurang, pengetahuan pasien masih kurang, dan perilaku (kepatuhan diet, aktivitas fisik, kepatuhan minum obat) pasien DM tipe 2 masih banyak yang tidak patuh, dan lebih tingginya prevalensi kadar glukosa darah tidak terkontrol dibandingkan yang terkontrol. Disarankan untuk lebih memaksimalkan peran TPG dalam pelayanan di pojok gizi (POZI) dan sebaiknya pelayanan di pojok gizi tidak hanya diperuntukkan untuk bayi, balita ataupun ibu hamil saja, tetapi juga difungsikan untuk melayani pasien penderita penyakit lain, khususnya pasien penderita DM serta diharapkan adanya penelitian lebih lanjut mengenai intervensi pada pasien penderita DM.